Optimum and effectiveness of adenosine deaminase level for pleural tuberculosis screening - Tanwarawutthikul, Poonyapa (Journal of Medical and Public Health Region 4, 2023)
Pleural tuberculosis (PTB) is a form of extrapulmonary tuberculosis (EPTB) that affects organs outside the lungs. Diagnosis of PTB is challenging due to low levels of Mycobacterium tuberculosis in pleural effusion, leading to misdiagnosis. Adenosine deaminase (ADA) has been increasingly used for diagnosis, but cutoff values for diagnosis vary depending on disease prevalence. This retrospective study aimed to determine the optimal cutoff value of ADA for screening PTB in pleural effusion. The study statistically analyzed data from 316 patients who underwent pleural effusion ADA testing, including 105 PTB. The median (interquartile range) of ADA level in patients with PTB was significantly different from that in non-PTB patients (p <0.05), with values of 68.30 (44.80 to 84.70) U/L and 29.10 (23.70 to 36.50) U/L, respectively. The optimal cutoff value of ADA for differentiating PTB from non-tuberculous pleural effusion was 38.60 U/L, with an area under the ROC curve (AROC) of 0.901, sensitivity of 82.86%, specificity of 81.52%, positive predictive value of 69.05%, and negative predictive value of 90.53%. In conclusion, utilizing ADA levels from pleural effusion is a simple, cost-effective, and highly sensitive method for screening pleural tuberculosis in comparison to the standard technique of TB culture, which is time-consuming and exhibits low sensitivity.